(3YLGFH GdBKGQ aj GdJQGLe hGdCNHGQs - (3YHO GdQMef Hf MSf GdLHQJj GdeUQj GdMfaj,J (B1237 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdbOje GdChd GdPj dGjRhd edcg hdG jJMhd s
(3BNQgG (B:s
(3hgPG BNQ eG jSQg Gddg dj ef JOhjfg aj gPg GdSfI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B304 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B133s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B480 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B730 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B284 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJGQjNs